Karang Lunak (Octocorallia: Alcyonacea) di Perairan Biak Timur - Anna Eliseba Wildamina Manuputty, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The Common Soft Corals (Octocorallia: Alcyonacea) in East Biak Waters. Soft corals are tentacle-bearing invertebrates that belong to the phylum Coelenterata. The name soft corals rever to Octocorallia which have nonmassive skeleton as internal axis. Their polyps always bear eight tentacles, which are fringed by one or more rows of pinnules along both edges. Samples of soft corals commonly found in shallow tropical waters have been collected from East Biak, Papua, in 2013. Sampling was conducted in 13 observation points, using SCUBA diving, from coastal waters to a depth of 20 m. This study aimed to determine the diversity and taxa composition of soft coral community in East Biak waters. A total of 18 genera were collected, including 3 new genera for these waters, namely Dampia, Paraminabea, and Capnella, which are described and discussed in detail in this paper, in addition to the distribution and abundance of individuals.. These genera have already been recorded from East Indonesian waters, but only found in the waters of East Biak at the time of this study. Notes on their distribution and abundance on the reefs are presented. Diversity index was moderate, ranging from 0.699 to 2.477, in which the highest value was recorded in station BIAL T1. Some genera of the family Nephtheidae dominated the observation locations and formed colonies of the same genus with a quite large dispersion